An investment model of social capital with empirical application to women's labour market outcomes in urban China - Yueh, L (University of Oxford, 2001)
The move to a more market-oriented economy is associated with evidence of increased inequality in the incomes earned by men and women. The context of our study of this question is the recent large-scale reform of the inefficient state sector, which has caused layoffs of urban workers that dramatically changed the state of employment in urban China. One factor in determining success in an imperfect labour market could be related to guanxi, the Chinese variant of social capital. We develop a model of social capital in which the decision to invest in guanxi is a function of time and resources expended, which may reflect and cause gender differences. Our original measures of social capital are created with a data set administered in urban China in early 2000. We find that there are gender differences in the stock of social capital and returns within the labour market. Women have less social capital than men and also lower economic returns in terms of earned income.